2021
DOI: 10.1126/sciadv.abf5851
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic auxotrophy remains stable after continuous evolution and in coculture with mammalian cells

Abstract: Understanding the evolutionary stability and possible context dependence of biological containment techniques is critical as engineered microbes are increasingly under consideration for applications beyond biomanufacturing. While synthetic auxotrophy previously prevented Escherichia coli from exhibiting detectable escape from batch cultures, its long-term effectiveness is unknown. Here, we report automated continuous evolution of a synthetic auxotroph while supplying a decreasing concentration of essential bip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 64 publications
(61 reference statements)
1
11
0
Order By: Relevance
“…For example, researchers have inserted bipA ( l -4,4′-biphenylalanine) into the sites of various essential proteins to generate an escape probability of less than 2 × 10 –12 within 2 weeks. They demonstrated that low BipA concentrations could support the stability of engineered microorganisms within 100 days of evolution . In addition, ligand-dependent essential gene-based auxotrophies require essential genes to function only in the presence of synthetic ligands.…”
Section: Biocontainmentmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, researchers have inserted bipA ( l -4,4′-biphenylalanine) into the sites of various essential proteins to generate an escape probability of less than 2 × 10 –12 within 2 weeks. They demonstrated that low BipA concentrations could support the stability of engineered microorganisms within 100 days of evolution . In addition, ligand-dependent essential gene-based auxotrophies require essential genes to function only in the presence of synthetic ligands.…”
Section: Biocontainmentmentioning
confidence: 99%
“…218 An orthogonalized genetic central dogma strategy can overcome the deficiencies of auxotrophy. Utilizing artificial elements (XNA, 219 nonstandard amino acids (nsAA), 220 synthetic ligands, 221 etc.) and coding principles (orthogonal DNA replication, 222 transcription, 223 and translation processes) to achieve orthogonalization of the central genetic dogma, the survival or specific gene expression of engineered probiotics depends on non-natural synthetic substances to achieve biocontainment (Figure 6c).…”
Section: Orthogonal System-based Biological Containmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we also sought to develop a tightly biocontained version of Ec_Syn61∆3-SL because a virus-resistant strain might have a competitive advantage in natural ecosystems due to the lack of predating bacteriophages. Synthetic auxotrophy based on the engineered reliance of essential proteins on human-provided nonstandard amino acids (nsAAs), e.g., L-4,4'biphenylalanine (bipA), offers tight, likely escape-free biocontainment that remains stable under long-term evolution [30][31][32] . Therefore, we generated a recombination deficient (i.e., ΔrecA), biocontained version of Ec_Syn61∆3-SL bearing a bipA-dependent essential adk gene and the bipA aminoacyl-tRNA synthetase/tRNA-bipA CUA system, by first performing adaptive laboratory evolution on a recA knock-out Syn61∆3, and then replacing the genomic adk copy with its bipAdependent variant 33,34 (Methods).…”
Section: Creation Of An Amino-acid-swapped Genetic Codementioning
confidence: 99%
“…We should expect to understand before long the functions that have been altered in this organism, allowing it to grow on 5‐chlorouracil while being inhibited by thymine. This entails understanding how these chassis will behave in the long run, but we can be confident that there is some hope for stability as demonstrated in stable evolution after 100 days of an E. coli strain after continuous co‐culture with mammalian cells (Kunjapur et al ., 2021).…”
Section: A Future For In Vivo Microbial Studiesmentioning
confidence: 99%